2020
DOI: 10.7554/elife.51760
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and physical limitations on the breaching performance of large whales

Abstract: The considerable power needed for large whales to leap out of the water may represent the single most expensive burst maneuver found in nature. However, the mechanics and energetic costs associated with the breaching behaviors of large whales remain poorly understood. In this study we deployed whale-borne tags to measure the kinematics of breaching to test the hypothesis that these spectacular aerial displays are metabolically expensive. We found that breaching whales use variable underwater trajectories, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 63 publications
2
32
1
Order By: Relevance
“…Comparatively, the energetic cost of breaching for an 8 m basking shark weighing 2700 kg was estimated six times greater (63 to 72 kJ 10 ). These differences may be attributed to the sharks in the present study being smaller, with the cost of breaching found to increase with increasing body mass 15 . A breach likely constitutes approximately 0.05 to 0.09% of their daily metabolic cost, which ranged from 12.8 to 21.5 MJ per day 16 .…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…Comparatively, the energetic cost of breaching for an 8 m basking shark weighing 2700 kg was estimated six times greater (63 to 72 kJ 10 ). These differences may be attributed to the sharks in the present study being smaller, with the cost of breaching found to increase with increasing body mass 15 . A breach likely constitutes approximately 0.05 to 0.09% of their daily metabolic cost, which ranged from 12.8 to 21.5 MJ per day 16 .…”
Section: Resultscontrasting
confidence: 60%
“…The relatively low field metabolic rate that comes with being ectothermic makes energetically demanding behaviour relatively more expensive for sharks. Therefore, the costs of performing multiple breaches may accumulate more rapidly compared to endothermic whales, such as humpback whales ( Megaptera novaeangliae ), which have been recorded breaching 17 times in a 6.5 h deployment 15 . On average, sharks required an estimated 11.5 kJ (range 3–22 kJ) of mechanical energy ( ) to perform a breach, and expended the same for each breach, regardless of whether they breached once or several times (Wilcoxon rank sum test, W = 198.5, p = 0.87; = 11.5 to 11.8 kJ, = 9.98 to 10.3 kJ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, and because of its shorter duration, the metabolic power required during engulfment follows the opposite trend, namely: 324 kW (VGB) versus 142 kW (fluking), 157 kW versus 79 kW, and 48 kW versus 20 kW; or in terms of land mammals BMR, 12 (VGB) versus 5 (fluking), 9 versus 5 and 14 versus 6. Finally, and compared to surface breaching by humpback whales ( Segre et al 2020 ), the prey-approach expenditures by our 8 m humpback whale turn out three-times smaller given the lower maximal prey approach speeds reached, that is, as compared with the 6–7 m/s attained just prior to surface breaking.…”
Section: Resultsmentioning
confidence: 76%
“…Tail slaps are the most common surface behavior observed, most likely because they are not associated with high energetic costs Segre et al, 2020). Therefore, humpback whales may only resort to breaching when noise pollution (such as that caused by high vessel presence) increases, as the sound of breaching travels much farther than the noise of a tail or pectoral fin slap.…”
Section: Behavior Frequencymentioning
confidence: 99%